SAVING BEHAVIOUR AMONG INDUSTRIAL LABOURS THROUGH THE LENS OF EXPLORATORY STUDY - Kitipacharadechatron, Ronnakron; Ratchapolsit, Atsawaluk (RMUTT Global Business and Economics Review, 2021)
This paper aims to examine the construct reliability of the model, and indicate factors and components influencing to saving behaviour. The data was collected via an online questionnaire among industrial labours out of 458 individuals with simple sampling method. The descriptive statistics and inferential statistics with the confirmatory factor analysis were used in the analysis procedure. Based on results ravel that the CFA model both factors, and components consisted with the empirical saving behaviour among industrial labours. Considering on model found that the component of saving knowledge and component of saving objective had the outstanding effect with statistically significant on empirical saving behaviour of industrial labours.